2008
DOI: 10.1051/0004-6361:200809364
|View full text |Cite
|
Sign up to set email alerts
|

A new asteroseismic diagram of solar-like stars

Abstract: Aims. We attempt to develop a new asteroseismic diagram and investigate its characteristics, based on the ratio "r 01 " of adjacent, average, small separations. Methods. The ratio r 01 is defined following the asymptotic formula of stellar p-modes. Using the low-degree, theoretical, numerical value of adiabatic frequencies of stellar model, we compute the ratio r 01 and construct an additional asteroseismic diagram. Results. The additional asteroseismic diagram, which is similar to the C-D diagram (i.e. the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Christensen-Dalsgaard (1988) suggested that a plot of δν against ∆ν can be used to determine stellar ages. Modifications to this so-called 'JCD diagram' have been suggested by Mazumdar (2005) and Tang et al (2008). However, this method does not work for more evolved stars (White et al, in preparation).…”
Section: Agementioning
confidence: 99%
“…Christensen-Dalsgaard (1988) suggested that a plot of δν against ∆ν can be used to determine stellar ages. Modifications to this so-called 'JCD diagram' have been suggested by Mazumdar (2005) and Tang et al (2008). However, this method does not work for more evolved stars (White et al, in preparation).…”
Section: Agementioning
confidence: 99%
“…The most traditional asteroseismic diagram, which was proposed by Christensen-Dalsgaard (1984, 1988, 1993, is a very useful technique combining useful features of the frequency spectrum of stars to extract information about physical processes, for example helium and heavy element diffusion, in the stellar interior, that affect the frequencies. This well-known asteroseismic diagram exploits the fact that the average large separation of radial modes Δν 0 reflects the gross properties of a star, like its mass and radius, and the average small separation d 02 is more sensitive to the innermost layers of the star, and therefore to its evolutionary state (Mazumdar 2005;Tang et al 2008).…”
Section: Introductionmentioning
confidence: 99%